One-month alcohol abstinence national campaigns: a scoping review of the harm reduction benefits - Julia de Ternay; Pierre Leblanc; Philippe Michel; Amine Benyamina; Mickael Naassila; Benjamin Rolland (BMC, 2022)
Abstract Over the last decade, one-month alcohol abstinence campaigns (OMACs) have been implemented within the general population in an increasing number of countries. We identified the published studies reporting data on OMACs to explore the following aspects: profile of participants, rates and factors associated with the completion of the abstinence challenge, and outcomes and harm reduction benefits in participating in the challenges. We screened 322 records, including those found in the grey literature, and reviewed 6 studies and 7 Dry July Annual Reports. Compared to non-participating alcohol users, participants were more likely to be female, have a higher income, and a higher level of education. They were heavier drinkers and were more concerned by the consequences of alcohol on health and by their health in general. Participants who achieved the one-month abstinence challenge were lower drinkers and more likely to have registered on the campaign-related Internet communities. Both successful and unsuccessful participants frequently reported health benefits, including sleep improvement and weight loss. Successful participants were more likely to durably change their alcohol drinking habits. Overall, OMACs provide short- or mid-term harm reduction benefits for both successful and unsuccessful participants. Findings were limited by the paucity of studies, their observational nature, and heterogeneity in the features of the different national campaigns, which would probably gain in enhanced internationalization.